Insect assemblages and their preference for Lupinus albus and L. luteus - Nikolova I.; Georgieva N. (Irish Journal of Agricultural and Food Research, 2018)
While lupin has undergone extensive research to ascertain its suitability for growth as forage or grain legume crop, the present trend is for research to be centered on its applicability in the seed protein and oil industry. Study of the literature showed that no intensive study of the lupin insect fauna had been carried out in Bulgaria. The purpose of this study was to identify the insect assemblages associated with Lupinus albus and L. luteus, as well as the insect preference for them. Thrips sampling was made by the tapping-method, aphids were directly counted on the plants and the composition and population density of other species were recorded by sweepings. Insect fauna was studied for the first time in Bulgaria. The fauna was represented on L. albus by 64 species, belonging to eight orders, 28 families and 57 genera, including 23 beetles, 25 hemipteras, five thrips, three butterflies, three bees, one leaf aphid, two grasshoppers, one leafminer and one green lacewing. L. luteus had similar species composition but was less preferred by insects. The use of lupin cultivars with shorter and intense reproductive periods, with a lower content of crude protein and phosphorus, would give an environmentally friendly protection against insect pests, which would be suitable for an organic production system.